Chulalongkorn's Elephants: The Philippines in Asian History - Ocampo, Ambeth R (Archīum Ateneo, 2011)
Chulalongkorn's elephants are bronze elephants the King of Siam gave to Singapore and Java as gifts during his travels in 1871. I met the Singapore elephant first as I traced Rizal's footsteps and found a reference to it in his diary. It was upon meeting next the Jakarta elephant that prompted me to compile this collection of essays that begins and ends with an elephant. More reflective than usual and going beyond Rizal and my 19th century comfort zone, these explorations still carry my trademark irreverent humor.